The mathematical simulation of the liquid transport in a multilayered nonwoven - Čiegis, Raimondas; Zemitis, Aivars (Mathematical Modelling and Analysis, 1997)
In this report we treat an optimization task, which should make the choice of nonwovens for making diapers faster. A mathematical model for the liquid transport in nonwoven is developed. Finite‐difference schemes are proposed for numerical solving of the differential problem. Parallel algorithms are considered and results of numerical experiments are given. First Published Online: 14 Oct 2010